Effects of magnetohydrodynamic mixed convection on fluid flow and structural stresses in the DCLL blanket. (June 2019) - Liu, Zhi-Hong; Chen, Long; Ni, Ming-Jiu; Zhang, Nian-Mei
Highlights: Mixed convection and structural mechanical behaviors in DCLL blanket are studied. The effects of magnetic field, FCI's electrical and thermal conductivity are studied. Buoyancy effects reduce the thermal stresses of FCI structure and make the FCI safer. The law ( e B / 5 ) of magnetic field on MHD pressure drop of blanket is revealed. Abstract: In this study, numerical simulations are conducted to investigate magnetohydrodynamic (MHD) mixed convection for buoyancy-assisted flows under strong magnetic field and large volumetric heat sources in the Dual-Coolant Lead-Lithium (DCLL) blanket. A magnetic-convection code based on the finite volume method is developed and validated using benchmark solutions. A consistent and conservative scheme is applied to deal with the electric current conservation issues. The PISO algorithm on unstructured collocated meshes is employed to solve the N-S equations considering the Lorentz force effect. Deformations and stresses of flow channel insert (FCI) are analyzed using the finite element method (FEM). Cases with high Hartmann number of 9600–19, 200, high Reynold number of 31, 000 and high Grashof number of 3.5 × 10 11 are used in the numerical simulations. The buoyancy effects as well as electric conductivity of the FCI on poloidal flows in rectangular channel with a SiC FCI are analyzed, considering non-uniform exponential volumetric heat source and toroidal magnetic field. The deformation field and stress field of the FCI are calculated under MHD mixed convection effects. Results demonstrate that a reverse flow occurs near the cold wall in the bulk region, which is a special phenomenon resulted from buoyancy. Compared to MHD forced convection, buoyancy delivers enhanced temperature uniformity, a drastically changed velocity distribution, and a slightly elevated pressure drop. At the same time, the pressure drop between inlet and outlet has a linear relation with e B / 5 . Mixed convection temperatures is insensitive to FCI electrical conductivity, and only velocity near the cold wall appears sensitive. In the FCI, both magnetic field and electrical conductivity positively correlate with thermal stresses. Simulations also suggest the buoyancy effect reduces temperature difference across FCI and thermal stress.